Analisis De Los Ingresos Y Gastos De La Empresa Productos Alimenticios Del Norte, Proalinor Cia Ltda - Pilco Moyota, Jonny Rodolfo (2018)
In the world, the transformation companies are becoming more competitive every day, being the grass one of the most commercialized products, produced and consumed worldwide. Micro enterprise enterprises are those that dominate the business sector at the national level according to INEC data; said institute records that they are a total of 90.2% of businesses, followed by 7.7% of small and medium enterprises; the main activity of these is the trade with 36.6%, in services 40.8%, agriculture 10.6%, manufacturing 8.1%, construction 3.5% and in exploitation of mines and quarries 0.4%, few of the micro, small or medium enterprises carry a adequate record of your accounts, be they of assets, liabilities, assets, expenses and income, this causes that in the course of the years this type of company closes its doors. (INEC, 2014) It is important to emphasize that making a correct accounting record and good management of information, allows any company or institution to obtain accurate and timely results, this in turn helps to simplify administrative or financial decisions. In the company "Productos Alimenticios del Norte CIA LTDA", the following situations were presented: there is inadequate control and recording of income and expenses, ignorance of the real profitability of the products sold based on the investment. Inappropriate management of income and expense accounts does not allow for control